Reproductive and Maternal Health in the Post-2015 Era: Cervical Cancer Must Be a Priority - Singhrao, Ruby; Huchko, Megan; Yamey, Gavin (PLOS Medicine, 2013)
Ruby Singhrao and colleagues propose four arguments for why cervical cancer screening and treatment should be prioritized. Please see later in the article for the Editors' Summary